모 - 자 (母 - 子) 상호작용에 있어서 아동의 자기 - 조정에 관한 연구 - 박찬화(Chan Hwa Park) (Korean Journal of child studies, 1987)
The purpose of the present research was to study the self-regulation of the child during mother child interaction. That is. this study focused on how mothers regulated children's problem solving efforts before children began to function as independent agents capable of self-regulation. The emphasis was on the "regulation-by-others" that preceded "self-regulation". The subjects of this study were 30 mother-child dyads. The dyads were divided into 3 groups of 10 dyads each on the basis of the child's age (2, 3, and 4 years of age). The instrument used for this study was the "truck puzzle" devised by Wertsch, McNamee, Mclane and Budwig (1980). The problem solving task in this study required the dyad to make a puzzle in accordance with the model puzzle. The interaction of 30 mother-child dyads was observed and analyzed flH verbal and non-verbal behavior used by the mother to regulate the child's behavior. One-way ANOVA, Scheffe post hoc comparision and Spearman's rank-difference correlation were used for the statistical analysis of the data. The results revealed that there were significant age trends in regulation-by-others and self regulation in joint cognitive activity; that is, there were developmental transitions from regulation by-others to self-regulation in connection with crucial strategic behavior (looking at the model). Significant differences were found in mothers' interventions after children's gaze at the model in joint cognitive activity; that is, the mean proportion of mothers' intervention for the 2-year-old group was the highest and that of the 4-year-old group was the lowest. There were no significant age-related differences in mothers' use of referential perspectives in joint cognitive activity. Children's regulation- by-others increased and children's self-regulation decreased in proportion to mothers' use of referential perspectives.